Towards Non-invasive Adaptive Meta-Cognitive Support for Online Training - WADE, VINCENT PATRICK; DAGGER, DECLAN; CONLAN, OWEN; MOORE, ADAM (IEEE, 2011)
Online training is an increasingly important facet of the skills enhancing portfolio of any organization and has an especial place within life-long learning, career development and other self-regulated adult learning. We here present an overview of work towards developing online training, which is augmented by contextual cues, training which is personalized and adapted, in real-time, towards the learning objectives of the user, whilst supporting a wide range of meta-cognitive activities. This work brings technologies developed for the fantastical scenarios of serious gaming into the 'real world' - we also begin to address some of the underlying challenges in this transition.
PUBLISHED
Keywords: Communications & Intelligent Systems; Digital Research; Informatics; life-long learning